ANALISIS PREFERENSI SISWA MELANJUTKAN KE SMK NEGERI 3 PEKANBARU T.P 2014 /2015 - Natalia Panjaitan Natalia Panjaitan; Rosmawati '; Abu Asyari Abu Asyari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This research has three arms : 1. To analyze students preferention factors to study at SMK Negeri 3 Pekanbaru. 2. To analyze dominan factors which is preferention for the student to study at SMK Negeri 3 Pekanbaru. 3. To know wich preferention category to study at SMK Negeri 3 Pekanbaru.The methode for the research is random sampling. And the research found that the must preferention factor  for student to study at SMK Negeri 3 Pekanbaru is to have a skill at work, it is about 100 %. The dominant factor is that SMK able to train the student businessmen it is about 96,7 % for high category it about 46,6 %, medium category it about 42,2 % and low category it about 11,1 %. Keyword:Preference